Some Biological Effects of Carbamoyloxyurea, an Oxidation Product of Hydroxyurea - Rosenkranz, Herbert S. (1970)
Carbamoyloxyurea, an oxidation product of hydroxyurea, is bactericidal for Escherichia coli. Drug-induced killing is independent of cellular metabolism; ribonucleic acid and protein syntheses are the processes most affected, and the lethal action is accompanied by degradation of cellular deoxyribonucleic acid. In all of these effects the drug differs from hydroxyurea, a primarily bacteriostatic agent that inhibits deoxyribonucleic acid synthesis, whose lethal action ultimately depends on cellular activity.